Selective Complexation Leaching of Rare Earth Minerals: A New Hydrometallurgical Route Inspired by Geochemical Process - Lazo, Daniel Eduardo (Curtin University, 2019)
This present study was intended to determine the potential of organic acids in REEs, specifically in monazite concentrate. The proposed process in this study consisted of a pre-treatment, leaching and RE hydroxide precipitation stages. The first stage consisted of producing rare earth (RE) oxalates by leaching monazite concentrate with oxalic acid. The second stage involved the extraction of the metals from the residue. The third stage involved the conversion of RE oxalate EDTA complex in the solution to a RE hydroxide.